Between the institution and the revolution: Intellectuals and political change in Mexico - Baca Olamendi, Laura (1997)
Before beginning the analysis of the role of intellectuals and their relationship with the State, we consider it pertinent to make some clarifications referred, above all, to the different definitions used to conceptualize the work of the intellectual. In this sense, it is possible to identify some interpretations that oppose intellectual work to manual work, and others that restrict it only to great thinkers, considered by the universality of their ideas the only and true intellectuals.